IMPROVING THE EFFICIENCY OF FUNCTIONING OF REPAIR-OPERATING UNITS IN THE SYSTEM OF MAINTENANCE AND REPAIR OF MAGISTRALS - Grudz, V. Y.; Grudz, V. V.; Bodnar, V. M.; Chernetsky, M. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The classification of failures and damages of the linear part and its separate elements is carried out, variants of technology of carrying out of preventive and repair-restoration works and modular-technological structure of repair and maintenance units are formulated. Particular attention is paid to improving the efficiency of the operation of a separate repair and maintenance unit during maintenance and repair with a known layout scheme and a certain mode of control and restoration works by choosing the optimal technology of work and rational equipment of units and crews leaving for the route. On the basis of the analysis of the technology of work execution it is shown that only a small part of the repair and maintenance measures requires the use of powerful machinery and equipment, which include the first level of priority work on the replacement of gas pipeline sections, work, damage elimination, work on elimination of significant pipeline displacements, work for restoration of soil collapse of the main gas pipeline. In addition, each type of work on the objects of the linear part requires the use of the same vehicles. The type and number of vehicles depend on the particular operating conditions, as well as on the possibility and feasibility of purchasing and operating a particular type of equipment. The method of estimation of indexes of maintenance of linear part of main gas pipelines and efficiency of functioning of repair and maintenance units during maintenance and repair is developed.